EVALUATION OF THE ANTIOXIDANTS CONTENT IN AQUEOUS EXTRACT OF LEAVES OF VEPRIS VERDOORNIANA (RUTACEAE) - LOHOUES EEC; TREBISSOU JND; AKA J; KONAN AML; DJINHI J; YAPI HF; ADIMA A (International Journal of Pharma and Bio Sciences, 2014)
Our objectives is to determine the antioxidant compounds content in the aqueous extract of leaves of Vepris verdoorniana (Rutaceae).We determined the content of phenolic and flavonoid compounds colorimetric methods and Folin-Ciocalteu method were used respectively. This plant extract contains phenolic and flavonoid compounds in 0.01N concentration of water / citric acid solution and water / sulfuric acid solutions. With the water / citric acid solution, the maximum level of phenolic and flavonoid compounds is 100 µg GA eq / L and 40 µg Isorham eq / L respectively. In the water / sulfuric acid solution they are 210 GA eq/ L and 30 µg Isorham eq / L.We concluded that Vepris verdoorniana (rutaceae) extract contains phenolic compounds and flavonoids involved in the removal of free radicals from the body. This plant can be used to find a cure against oxidative stress.